Hemodialysis Treatment for High-Dose Quetiapine Fumarate Poisoning: A Case Report - Jiaoyang Li; Zhiqin Chen; Shuran Qian; Xuemei Liu (Case Reports in Nephrology and Dialysis)
Introduction: Quetiapine is a new atypical antipsychotic with minor side effects. There have been few reports of rhabdomyolysis and acute kidney injury associated with quetiapine overdose. Case Presentation: This article presents a rare case of high-dose quetiapine poisoning that improved after treatment. The patient experienced rhabdomyolysis, acute kidney injury, long QT syndrome, and peripheral neuropathy, all of which are typical complications of quetiapine poisoning. Moreover, a kidney biopsy verified the patient’s acute tubulointerstitial injury, and immunohistochemical staining demonstrated that myoglobin cast nephropathy was the cause of the injury. This patient’s kidney function and associated complications recovered after receiving hemodialysis, rehabilitation, heart rate regulation, and further symptomatic interventions. Consequently, hemodialysis was discontinued. Conclusion: Our case showed that myoglobin cast nephropathy was the cause of the acute kidney injury associated with quetiapine poisoning. The kidney biopsy is essential for accurate diagnosis and treatment.